2017
DOI: 10.3343/alm.2017.37.2.151
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Virus Serotypes Circulating in Khyber Pakhtunkhwa Province, Pakistan, 2013-2015

Abstract: From 2013 to 2015, the National Institute of Health, Pakistan, received 1,270 blood samples of suspected dengue cases reported from inpatient and outpatient departments of various hospitals in Khyber Pakhtunkhwa (KPK) province. In this study, we determined the circulating dengue virus (DENV) serotypes using real-time reverse transcriptase (RT)-PCR to understand the serotype-based epidemiology of DENV. All four serotypes (DENV-1 [6%], DENV-2 [33%], DENV-3 [47%], and DENV-4 [0.1%]) were found circulating during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 14 publications
3
14
1
Order By: Relevance
“…The infection rate in males was double as compared to female, with a male to female ratio of 2:1, an observation that corresponds with previous results from studies of the Khyber Paktunkhwa province (Suleman et al, 2016). This epidemic disease transferred from Swat to nearby areas including the Malakand, Kohat, Mansehra districts, lower and upper Dir, Peshawar (Suleman et al, 2017) and then other districts like Mardan, Nowshera and Swabi. In Peshawar 11,685 infected people's cases were registered till to 7 November 2017 (Gubler, 1998) and 7 deaths were recorded till to 22 August according to the Dawn News.…”
Section: Introductionsupporting
confidence: 87%
“…The infection rate in males was double as compared to female, with a male to female ratio of 2:1, an observation that corresponds with previous results from studies of the Khyber Paktunkhwa province (Suleman et al, 2016). This epidemic disease transferred from Swat to nearby areas including the Malakand, Kohat, Mansehra districts, lower and upper Dir, Peshawar (Suleman et al, 2017) and then other districts like Mardan, Nowshera and Swabi. In Peshawar 11,685 infected people's cases were registered till to 7 November 2017 (Gubler, 1998) and 7 deaths were recorded till to 22 August according to the Dawn News.…”
Section: Introductionsupporting
confidence: 87%
“…Although not all these viruses were responsible for VHF, we screening these viruses due to many studies were conducted in eastern Sudan revealed the presence of highly seropositive of dengue and HEV [33,[43][44][45]. Thirteen patients were positive for dengue IgM in ELISA, although the PCR results for all DFV types were negative, which may be explained by the presence of several genetically and antigenically different serotypes of the DFV worldwide [6,7,43,[46][47][48]. Mosquito-infested areas show high rates of malarial parasite infection.…”
Section: Discussionmentioning
confidence: 98%
“…Globally, vector-borne diseases are responsible for more than 20% of the infectious diseases affecting all humanity worldwide, most commonly in the developing countries in Africa and Asia; many African communities suffer from vector-borne disease burden and its socioeconomic consequences [2][3][4][5]. Mosquito-borne viruses affecting humans, these viruses include: chikungunya (CHIKV), dengue fever (DFV), yellow fever (YFV), Rift Valley fever virus (RVFV), Sindbis virus (SINV), and alkhurma viruses [2,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Dengue virus (DENV) infection is a mosquito-borne disease that constitutes one of the major public health problems in subtropical and tropical areas [12]. As many patients either have no symptoms or present with nonspecific fever requiring differential diagnosis, laboratory confirmation using a rapid, accurate, and relatively low-cost diagnostic test is especially important [3].…”
mentioning
confidence: 99%